CURRENT DEFICIENCIES IN FINANCIAL STATEMENTS. - Werntz, William W. (The Accounting Review, 1941)
Abstract The article presents information about current deficiencies in financial statements. One of the principal functions of the U.S. Securities and Exchange Commission is to make available to investors reasonably complete and accurate information about the business affairs of issuers whose securities are listed on national securities exchanges and issuer whose securities are publicly offered for sale in interstate commerce or through the mails. To this end, the Securities Act requires such issuers to file with the commission reports that are designed to furnish some of the basic information needed in appraising these securities. The Commission's examination of these filings culminates either in their becoming effective without amendment or in the issuance of a memorandum which will either cite deficiencies to be corrected by amendment of the instant filing, or note suggestions to be observed in the preparation of future filings. Failure to correct deficiencies cited may result in stop-order or delisting proceedings.